Віртуальна система енергетичного управління енергозабезпеченням регіональної інфраструктури - Eutukhova, Tatiana; Novoseltsev, Oleksandr (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The main purpose of this study is to present in an integrated form a conceptual framework (platform) for the implementation of an energy management system in the environment of virtual organizations (VOs), which allows to expand the scope and improve the quality of energy management services by combining the resources, capabilities, and information of members of the VO business community. One of the key tasks of improving energy management systems is the active use of cloud-based information and communication technologies to increase the efficiency of energy management measures at all stages of their implementation, including those related to the actions of personnel to control the operating modes of technological equipment. At the same time, the implementation of these tasks in the virtual space requires a fundamental change in the structure and nature of the interaction between energy management service providers and their clients. In this vein, a careful balance between efforts to improve energy efficiency and ensure the fulfillment of the client's core missions are prioritized. The goals are achieved through systematic coordination of the design, procurement, installation, and operation of energy-efficient equipment, monitoring, and verification of the results achieved, taking into account environmental and economic parameters. Among the main advantages of using virtual energy management services, first of all, we would like to highlight their opportunities for further development of the service market, which are realized by: 1) improving the efficiency of service provision, 2) more sustainable and reliable investment attraction, 3) use of renewable energy sources, cogeneration, heat pumps, energy storage, etc., 4) customer load management, 5) organization of portfolio supplies and use of distributed generation, 6) simplification of the procedure for effective search and selection of partners, and 7) establishment of fair competition. Based on the results of the study, the paper develops two main tools. These are the organization of systemically coordinated virtual interaction of service-oriented providers with customers and the creation of their virtual business community, where energy service companies (ESCOs) are considered the leading performers. In this sense, considerable attention is paid to the creation of a virtual center for coordinating ESCOs activities, the procedure for solving problematic issues of financing ESCO projects is presented, the mechanism and scheme of ESCO cooperation in cross-border (heterogeneous) markets are considered, and conclusions are drawn on the advantages of using VO's energy management services.